Cytotoxic CD8+ Temra cells show loss of chromatin accessibility at genes associated with T cell activation - Türk, Lehte; Filippov, Igor; Arnold, Christian; Zaugg, Judith; Tserel, Liina; Kisand, Kai; Peterson, Pärt (Frontiers in Immunology, 2024)
As humans age, their memory T cell compartment expands due to the lifelong exposure to antigens. This expansion is characterized by terminally differentiated CD8+ T cells (Temra), which possess NK cell-like phenotype and are associated with chronic inflammatory conditions. Temra cells are predominantly driven by the sporadic reactivation of cytomegalovirus (CMV), yet their epigenomic patterns and cellular heterogeneity remain understudied. To address this gap, we correlated their gene expression profiles with chromatin openness and conducted single-cell transcriptome analysis, comparing them to other CD8+ subsets and CMV-responses. We confirmed that Temra cells exhibit high expression of genes associated with cytotoxicity and lower expression of costimulatory and chemokine genes. The data revealed that CMV-responsive CD8+ T cells (Tcmv) were predominantly derived from a mixed population of Temra and memory cells (Tcm/em) and shared their transcriptomic profiles. Using ATAC-seq analysis, we identified 1449 differentially accessible chromatin regions between CD8+ Temra and Tcm/em cells, of which only 127 sites gained chromatin accessibility in Temra cells. We further identified 51 gene loci, including costimulatory CD27, CD28, and ICOS genes, whose chromatin accessibility correlated with their gene expression. The differential chromatin regions Tcm/em cells were enriched in motifs that bind multiple transcriptional activators, such as Jun/Fos, NFkappaB, and STAT, whereas the open regions in Temra cells mainly contained binding sites of T-box transcription factors. Our single-cell analysis of CD8+CCR7loCD45RAhi sorted Temra population showed several subsets of Temra and NKT-like cells and CMC1+ Temra populations in older individuals that were shifted towards decreased cytotoxicity. Among CD8+CCR7loCD45RAhi sorted cells, we found a decreased proportion of IL7R+ Tcm/em-like and MAIT cells in individuals with high levels of CMV antibodies (CMVhi). These results shed new light on the molecular and cellular heterogeneity of CD8+ Temra cells and their relationship to aging and CMV infection.